White flowers near Owl Creek - Kaplan, Nicole, photographer (Colorado State University. Libraries, 2009)
White flowers below cottonwoods in Owl Creek drainage on the SGS, windmills on buttes in distance.
Keywords: flowers; windmills; landscapes; plants; SGS; Owl Creek; buttes